Development of corporate governance performance indicators for Czech manufacturing companies - Marie Pavláková Dočekalová (DANUBE: Law, Economics and Social Issues Review, 2015)
Effective corporate governance is a key element in achieving long-term success for any company. The codes of conduct that corporate governance adopts directly determine the sustainability of business activities. With this in mind, this paper aims to demonstrate the results of research that identifies a set of key indicators of corporate governance performance. The presented research is quantitative. In order to identify key performance indicators, factor analysis was employed. It was found that corporate governance performance is influenced by two factors. For the first factor, the relationship between corporate governance and stakeholders is measured by key indicators: percentage of women within CG, contributions to political parties, politicians and related institutions and number of complaints received from stakeholders. The second factor, strategy & compliance, is generated from the following: percentage of strategic objectives met and total number of sanctions for breaching the law. This research aims to assist both academic and corporate practitioners who want to improve corporate governance performance and, through the use of key performance indicators, support the transparency and sustainability of their business.
Keywords: 330; Corporate governance; key performance indicators; sustainability; factor analysis